A comparative study between the UK and the USA house price indicators before and during the financial crisis of 2007-2009. Issue 4 (18th October 2018) - Benamraoui, Abdelhafid
Abstract : Purpose: This paper aims to examine the relationship between key economic fundamentals and average house price (AHP) movements before and during the financial crisis of 2007 to 2009 in the UK and the USA. Design/methodology/approach: Multiple regression analysis is applied in assessing the correlation between AHPs and a set of selected economic fundamentals. Findings: The study results show that earnings and to less extent interest rate have the highest correlation with the AHP and among the different types of interest rate used variable interest rate has the strongest correlation with AHP. The results also reveal that most indicators behave in the same way both before and during the financial crisis, but with better explanatory power for the pre-crisis period. Another key finding is that the directions of relationship for some of the parameters have changed when the market is in crisis, especially in the case of loans extended to house purchase for the UK market and number of households for the US market. Originality/value: The originality of the paper stems in using a wide range and thoroughly selected economic fundamentals to explain the movement in house prices and to observe the effect of financial crisis on the correlation between each economic factor and house price movements. The study is also unique in comparing the UK and the US housing markets for the time frame under consideration and for the economic parameters used.